IPTEK BAGI MASYARAKAT PADA KELOMPOK TANI TERNAK DI SUNGAI PERMAI, LAMBUNG BUKIK - Evitayani Evitayani; Yetti Marlida; Ahadiyah Yuniza; James Hellyward; , Suyitman , Suyitman; Harnentis Harnentis (Jurnal Hilirisasi IPTEKS, 2018)
West Sumatra Province has relatively extensive agriculture with feed ingredients such as rice straw, Rumput Gajah and legume groups that can be used for beef cattle needs. The total area of Padang City is 694.96 km², and more than 60% of this area, about ± 434.63 km² is a hilly area covered by protected forests, while the rest is an effective urban area. While the topography of the city varies, 49.48% of the land area of Padang City is in a slope of more than 40% and 23.57% is in the slope of the slope. The eastern region consists of several sub-districts, starting from north to south, respectively from Koto tangah, Pauh, Kuranji, and Lubuk sub-districts. The Pauh region, such as the village of Lambung Bukik, belongs to the Pertides forum program (universities for villages) which collaborates with the 2019 Chancellor's MOU with the Ministry of Education PDTT) to prepare and implement programs to help build villages. Some of their income is obtained from raising livestock and farming. In general, both agricultural and livestock businesses are still carried out traditionally, so it is not surprising that the results obtained are relatively low. Cows are only ground or tethered at night, while in the afternoon they are released to look for food on the grass or in the sleeping area around the village. Only a small amount of effort has been made to raise livestock intensively by supplying and providing sufficient and regular food. The low level of livestock production is caused by the lack of knowledge of farmers in the proper way of raising livestock, also because of the lack of food both forage and the high price of concentrate. With the increase in the livestock population, it certainly requires more and sufficient forage throughout the year. However, the provision of forage has experienced serious obstacles. One of them is the existence of a dry season that causes a decrease in forage production. Therefore, the business of developing beef cattle will be more profitable if you can find alternative substitutes for conventional forage with the use of silos as feed fermentation sites. The use of agricultural products (such as rice straw) and other food crops as animal feed is expected to address the above problems. This is possible because cattle breeding is generally integrated with other farming businesses, especially food crops (rice fields) so that the results of agricultural follow-up will be available throughout the year. Therefore, there is a need for a kind of touch of feed technology with the use of agro-industry by products such as straw which are proven to be available at all times. The implementation of the application of rice straw ammoniation technology in the field with the direct administration of ammonia which has been removed and chicken manure is given. Participation and motivation of farmer groups in participating in a series of service activities is very high. Because all this time there has never been any guidance related to the technical and management aspects in the maintenance of beef cattle. Farmers already know how to manage fattening beef cattle such as giving concentrates such as coconut cake, soybean meal, fish meal, tofu pulp and bran and giving premix minerals.